Enantiospecific formal synthesis of inthomycin C - Athawale, Paresh R.; Kashinath, K.; Reddy, D. Srinivasa (Chemistry Select, 2016)
An enantiospecific synthesis of Hatakeyama's intermediate enynol has been accomplished in both enantiomeric forms. As these intermediates can be converted to (3R)-inthomycin C and (3S)-inthomycin C through respective enynol intermediates using reported procedures, present effort may be regarded as formal synthesis of inthomycin C in both enantiomeric forms. Our synthesis highlights the use of pantolactone chiral pool and thus reconfirms the previously assigned absolute stereochemistry as 3R to the natural product inthomycin C.

Total synthesis of the marine natural product solomonamide B necessitates stereochemical revision - Kashinath, K.; Jachak, Gorakhnath R.; Athawale, Paresh R.; Marelli, Udaya Kiran; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Organic Letters, 2016)
The first total synthesis of the proposed structure of solomonamide B has been achieved. However, the H-1 and C-13 NMR spectral data of the synthesized compound was not exactly matching with that of the natural solomonamide B. This prompted us to revise the originally proposed structure, in particular, the stereochemistry of the nonpeptide part, which was confirmed by its total synthesis. During the course of the synthesis, we have developed an interesting hydroxy group directed Wacker oxidation of internal olefins in a macrocyclic setting.

Efforts to access the potent antitrypanosomal marine natural product janadolide: synthesis of des- tert -butyl janadolide and its biological evaluation - Athawale, Paresh R.; Jachak, Gorakh; Shukla, Anurag; Shanmugam, Dhanasekaran; Reddy, Srinivasa (ACS Omega, 2018)
To identify novel antitrypanosomal agents based on Janadolide, a potent macrocyclic polyketide–peptide hybrid, a macrolactonization strategy was explored. We prepared des-tert-butyl Janadolide and evaluated its antitrypanosomal activity. Our findings suggest that the tert-butyl group is necessary for the desired bioactivity.

Total synthesis of the potent anti-inflammatory natural product solomonamide A along with structural revision and biological activity evaluation - Jachak, Gorakhnath R.; Athawale, Paresh R.; Agarwal, Heena; Barthwal, Manoj Kumar; Lauro, Gianluigi; Bifulco, Giuseppe; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2018)
Herein, we report the total synthesis of solomonamide A along with its structural revision for the first time. The natural product possesses very potent anti-inflammatory activity, and it contains a macrocyclic peptide having four consecutive stereocenters on an unnatural amino acid component. The key features in the present synthesis include the application of an Evans aldol reaction, ligand-free Heck macrocyclization and chemoselective oxidations. The challenging task of fixing the stereochemistry of OH at the C5-position was accomplished with the help of DFT calculations, applying a quantum-mechanical (QM)/NMR combined approach. Biological evaluation in a mouse paw edema model revealed that a low dose (0.3 mg kg(-1)) of the synthesized solomonamide A showed 74% reduction at 6 h, which was comparable to a high dose (10 mg kg(-1)) standard drug dexamethasone effect (75% at 6 h). Thus, we further confirmed the revised structure of solomonamide A.

Access to a stereoisomer library of solomonamide macrocycles - Jachak, Gorakhnath R.; Athawale, Paresh R.; Choudhury, Rahul; Kashinath, K.; Reddy, D. Srinivasa (Chemistry-An Asian Journal, 2019)
In an attempt towards understanding stereo-structure activity relationships (SSARs), we have prepared eight possible stereoisomers of solomonamide macrocycles, in particular, by changing the stereochemical pattern of non-peptide fragment AHMOA. Here, we have demonstrated different ways to construct three contiguous chiral centers present in solomonamide B macrocycle using substrate/reagent-controlled methods. These methods involve Brown crotylation, NHK reaction and Evans aldol addition as key steps to synthesize key non-peptide fragment. Further, these non-peptide fragments were converted to their corresponding macrocycles via ligand-free intramolecular Heck reaction.
Keywords: Crotylation; Heck reaction; Inflammation; Macrocycles; Stereochemistry

Neural anti-inflammatory natural product periconianone A: total synthesis and biological evaluation - Kalmode, Hanuman P.; Patil, Suhag S.; Handore, Kishor L.; Athawale, Paresh R.; Dandela, Rambabu; Verma, Abhishek Kumar; Basu, Anirban; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2019)
Total synthesis of periconianone A, an eremophilane-type sesquiterpenoid with impressive neural anti-inflammatory potential, has been accomplished. Diels-Alder/aldol strategy to construct tetrahydro-naphthalene-2,6-dione scaffold, allylic oxidation of dienone using DBU/O-2 and postulated biomimetic aldol reaction to construct 6/6/6 tricyclic system are the highlights of the present synthesis. Furthermore, the synthesized (+/-)-periconianone A and two close analogs were tested for their neural anti-inflammatory activity using various assays. In the course of our study we found a structurally simplified analog is superior to (+/-)-periconianone A.
Keywords: Aldol; Allylic oxidation; Biological evaluation; Cytotoxicity; Diels-Alder; Periconianone A

Overturning the peribysin family natural products isolated from periconia byssoides OUPS-N133: synthesis and stereochemical revision of peribysins A, B, C, F, and G - Athawale, Paresh R.; Kalmode, Hanuman P.; Motiwala, Zenia; Kulkarni, Kiran A.; Reddy, D. Srinivasa (Organic Letters, 2020)
Herein we report the stereochemical revision of peribysins A, B, C, F, and G, guided by enantiospecific total synthesis starting from (+)-nootkatone. Furthermore, we reconfirmed the absolute stereochemistry of peribysin Q The highlights of the synthesis are enone transposition and kinetic iodination resulting in separation of diastereomers. Our findings coupled with synthetic and biological data previously reported by Danishefsky's group suggest that the original stereochemistries of peribysins A, B, C, F, and G were misassigned.

DBU/O-2-mediated oxidation of dienones - Athawale, Paresh R.; Kalmode, Hanuman P.; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2021)
Herein, we describe a DBU/O-2-promoted novel method for oxidation of dienones to 2,6-dione derivatives. The reaction involves treatment of a dienone with DBU in acetonitrile employing molecular oxygen as the oxidant. Metal free conditions and an eco-friendly reagent are the striking features of this protocol. This transformation proceeds through a peroxide intermediate that upon Kornblum-DeLaMare rearrangement produces 2,6-diones. The method was successfully utilized for the synthesis of (+/-)-pleodendione with improved yields versus those of the traditional PDC-TBHP method.

Scalable, sustainable and catalyst-free continuous flow ozonolysis of fatty acids - Atapalkar, Ranjit S.; Athawale, Paresh R.; Reddy, D. Srinivasa; Kulkarni, Amol A. (Green Chemistry, 2021)
A simple and efficient catalyst-free protocol for continuous flow synthesis of azelaic acid is developed from the renewable feedstock oleic acid. An ozone and oxygen mixture was used as the reagent for oxidative cleavage of double bond without using any metal catalyst or terminal oxidant. The target product was scaled up to more than 100 g with 86% yield in a white powder form. Complete recycling and reuse of the solvent were established making it a green method. The approach is significantly energy efficient and also has a very small chemical footprint. The methodology has been successfully tested with four fatty acids making it a versatile platform that gives value addition from renewable resources.

Tuning of alpha-silyl carbocation reactivity into enone transposition: application to the synthesis of peribysin D, E-volkendousin, and E-guggulsterone - Athawale, Paresh R.; Zade, Vishal M.; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Organic Letters, 2021)
A reliable method for enone transposition has been developed with the help of silyl group masking. Enantio-switching, substituent shuffling, and Z-selectivity are the highlights of the method. The developed method was applied for the first total synthesis of peribysin D along with its structural revision. Formal synthesis of E-guggulsterone and E-volkendousin was also claimed using a short sequence.

Comprehensive study on solomonamides: total synthesis, stereochemical revision, and SAR studies toward identification of simplified lead - Jachak, Gorakhnath R.; Kashinath, K.; Vasudevan, N.; Athawale, Paresh R.; Choudhury, Rahul; Dange, Santoshkumar S.; Agarwal, Heena; Barthwal, Manoj Kumar; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2023)
Solomonamides, a pair of macrocyclic peptide natural products originating from marine sources, have garnered significant attention within the synthetic community owing to their marked anti-inflammatory efficacy and intricate molecular architectures. In this paper, we present a very detailed investigation into solomonamides, including the challenges associated with the total synthesis, the evolution of our synthetic strategies, structural reassignment, synthesis of all possible stereoisomeric macrocycles, biological assessment, structure-activity relationship (SAR) studies, etc. Within the ambit of this total synthesis, diverse strategies for macrocyclization were rigorously explored, encompassing the Friedel-Crafts acylation, cyclization involving the aniline NH2 moiety, macrolactamization utilizing Gly-NH2, and Heck macrocyclization methodologies. In addition, an array of intriguing chemical transformations were devised, including but not limited to photo-Fries rearrangement, Wacker oxidation, ligand-free Heck macrocyclization, oxidative cleavage of indole, synthesis of contiguous stereocenters via substrate/reagent-controlled protocols, and simultaneous making and breaking of olefinic moieties. The findings of this investigation revealed a structurally simplified lead compound. Remarkably, the lead compound, while possessing structural simplification in comparison to the intricate solomonamide counterparts, demonstrates equipotent in vivo anti-inflammatory efficacy.

Direct deoxygenation of α-hydroxy and α,β-dihydroxy ketones using a silyl lithium reagent - Zade, Vishal M.; Gangnale, Laxmikant D.; Athawale, Paresh R.; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2023)
A reliable method for the one-step direct deoxygenation of alpha-hydroxy ketones has been developed using a silyl lithium reagent and acetic anhydride. The method is metal-catalyst-free and does not require prefunctionalization of the hydroxy group prior to its removal. Deoxygenation of different primary, secondary, and tertiary alcohols was carried out with up to 98% isolated yield. Additionally, double deoxygenation was achieved when the present method was applied to alpha,beta-dihydroxy ketones to access the corresponding enones in a single step.

Synthesis of benzofuran-6-carboxylic acid, an intermediate of lifitegrast with low-carbon footprints - Zade, Vishal M.; Athawale, Paresh R.; Kopperi, Harishankar; Mohan, S. Venkata; Reddy, D. Srinivasa (ACS SUSTAINABLE CHEMISTRY & ENGINEERING, 2024)
Keywords: benzofuran-6-carboxylicacid; dry eye disease; life cycle; lifitegrast; process development